In-situ X-ray measurements of defect generation during PVT growth of SiC - Konias, Katja; Hock, Rainer; Stockmeier, Matthias; Wellmann, Peter; Miller, Michael; Ossege, Stefan; Magerl, Andreas (Materials Science Forum, 2007)
A standard inductively heated PVT growth furnace modified for diffraction experiments with high energy x-rays in focussing Laue geometry was built. The growth furnace will be placed in front of a tungsten anode high energy x-ray source. The Laue diffraction pattern of the growing crystal can be detected on a CCD camera detector. Evolution of crystalline defects as a function of the growth process parameters will be infered from the diffraction experiments. The furnace design and results of first test measurements serving as proof of concept are reporte
Keywords: PVT; crystal growth; growth furnace; x-ray diffraction; high energy x-rays; focussing Laue geometry; defects